Deposition of thin films on basalt fibers surface by atmospheric pressure plasma with different siloxane precursors - Chengfeng Xiong; Ming Gao; Hao Huang; Yu Wang; Xiaobin Gu; Zilan Xiong; Yifan Huang (Applied Surface Science Advances, 2024)
In this study, surface modification of basalt fibers (BFs) utilizing atmospheric pressure plasma deposition was carried out. Using this one-step deposition approach, three siloxane precursors with different structures including methyltrimethoxysilane (MTMS), hexamethyldisiloxane (HMDSO), and tetramethoxysilane (TMOS) were deposited on BFs surface, respectively. The physicochemical properties of the thin films from three different siloxane compounds are elucidated. In comparison with MTMS-coated sample, HMDSO-coated and TMOS-coated BFs surfaces feature an improved thermal insulation performance. The results demonstrate that atmospheric pressure plasma deposition is an efficient approach to modify flexible materials surface with improved thermal insulation. Moreover, it provides a reference to decide which precursor type is preferred for certain applications.